Colonialism and Islamic Modernism: Differences in the Development Paths of Islamic Boarding Schools in Indonesia - Asrori, Saifudin; Ismail, Muhammad (ILMU USHULUDDIN, 2023)
Islamic modernism emerged in the 19th and early 20th centuries as a response to global challenges, aiming to blend Islamic values with modern elements like science and technology. It spread globally in response to colonialism and modernization. In Indonesia, it developed during the transition to democracy, with regional autonomy leading to the implementation of Sharia in local regulations. Some radical groups in Indonesia sought to establish a strict Islamic state, driven by motives like the desire for a caliphate. In response, a liberal Islamic movement emphasizing contextual interpretations emerged. Islam Nusantara, represented by NU, exemplifies a moderate and tolerant form of Islam. Religious moderation is seen as an alternative to balance extreme interpretations, focusing on tolerance, democracy, and the rejection of violence. This article will delve into the journey of Islamic modernism, starting from its pioneers in Egypt and extending to Indonesia, where debates and developments in religious thought have become significant stages